2020
DOI: 10.1111/jon.12690
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Preoperative Bilingual Language fMRI Mapping in Patients with Brain Tumors

Abstract: BACKGROUND AND PURPOSE Previous literature has demonstrated disparity in the postoperative recovery of first and second language function of bilingual neurosurgical patients. However, it is unclear to whether preoperative brain mapping of both languages is needed. In this study, we aimed to evaluate the clinical utility of language task functional MRI (fMRI) implemented in both languages in bilingual patients. METHODS We retrospectively examined fMRI data of 13 bilingual brain tumor patients (age: 23 to 59 yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The volume of language activation in the left-dominant hemisphere in L1 was the same in those patients as in the monolingual controls [14]. Moreover, a study [92] involving bilingual patients with brain tumors found that fMRI language mapping performed in both languages provided a superior appreciation of the language network than mapping in only one language (i.e., more language-related regions were identified). This finding has been confirmed by a recent systematic review of studies with patients (including individuals with brain tumors) who underwent neurosurgical language mapping (pre-operative fMRI, Wada, and/or electrical stimulation mapping) [93].…”
Section: Linguistic Factorsmentioning
confidence: 75%
“…The volume of language activation in the left-dominant hemisphere in L1 was the same in those patients as in the monolingual controls [14]. Moreover, a study [92] involving bilingual patients with brain tumors found that fMRI language mapping performed in both languages provided a superior appreciation of the language network than mapping in only one language (i.e., more language-related regions were identified). This finding has been confirmed by a recent systematic review of studies with patients (including individuals with brain tumors) who underwent neurosurgical language mapping (pre-operative fMRI, Wada, and/or electrical stimulation mapping) [93].…”
Section: Linguistic Factorsmentioning
confidence: 75%
“…To the best of our knowledge, this is the first study to standardize a protocol for language mapping in Greek, while at the same time, this protocol is able to reliably activate a language system wider than the Wernicke–Lichtheim–Geschwind model. Apart from the Greek native speakers, this may prove important for Greek bilingual speakers in other countries undertaking neurosurgery, as many studies suggest that language areas near tumors activate more reliably in the native language when compared to the later acquired languages (Kuper et al., 2021 ; Leung et al., 2020 ; Protopapas et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, our study consisted of healthy volunteers only. Studies have shown that language laterality values can differ across languages in patients suffering from epilepsy or tumors 4,7 . Furthermore, L1 was found on cortical mapping to present more positive language sites than L2 and L3 in patient with high proficiency in foreign languages 13,25,26 .…”
Section: Language Organizationmentioning
confidence: 99%
“…At least more than half the world's population is bilingual 3 . Extensive research has been conducted on language organization in bilingual [4][5][6][7][8][9][10][11] and multilingual populations [12][13][14][15][16] . Several factors have been identified as playing a role in the organization of language in multilingual subjects.…”
mentioning
confidence: 99%